1992
DOI: 10.1051/forest:19920302
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to air embolism of three European oak species (Quercus petraea (Matt) Liebl, Q pubescens Willd, Q robur L)

Abstract: Summary — The vulnerability to water-stress induced cavitation and the petiole leaf specific conductivity (LSC) have been studied on excised branches of Quercus petraea, Q pubescens, Q robur and Q rubra. Seasonal evolution of xylem embolism in the petioles and twigs of mature Q petraea has been followed together with increasing soil water deficit. Field experiments showed that Q petraea suffered from embolism damage in both petioles and twigs after heavy drought. Large differences in terms of vulnerabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
3
16

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 11 publications
10
113
3
16
Order By: Relevance
“…When petioles reached 90% loss of hydraulic conductivity, the leaf water potential Ψ was approximately -1.9 MPa; at the same Ψ, the stems had lost only about 15% of their maximum hydraulic conductivity. This is in contrast to several Quercus, Fraxinus or Populus species where there is no difference in the VC of stems and petioles [18,20,22]. This study on walnut is the first case showing that drought-induced leaf shedding is preceded by cavitation in petioles before cavitation in stems, due to vulnerability segmentation.…”
Section: Examples Of Vulnerability Curvescontrasting
confidence: 55%
“…When petioles reached 90% loss of hydraulic conductivity, the leaf water potential Ψ was approximately -1.9 MPa; at the same Ψ, the stems had lost only about 15% of their maximum hydraulic conductivity. This is in contrast to several Quercus, Fraxinus or Populus species where there is no difference in the VC of stems and petioles [18,20,22]. This study on walnut is the first case showing that drought-induced leaf shedding is preceded by cavitation in petioles before cavitation in stems, due to vulnerability segmentation.…”
Section: Examples Of Vulnerability Curvescontrasting
confidence: 55%
“…8a), we observed that the maximum predicted PLC in the field approached 30%. Contrastingly, according to the vulnerability curve by [9], pressure causing a 50% loss of xylem conductivity in Q. pubescens was ca. −3.4 MPa (Fig.…”
Section: Vulnerability To Embolism and Relationships Between Hydraulimentioning
confidence: 86%
“…8a). At the same water potentials, Q. pubescens still maintained G s, md at 40% of its maximum value with a corresponding PLC of less than 10%, according to [9] (Fig. 8b).…”
Section: Vulnerability To Embolism and Relationships Between Hydraulimentioning
confidence: 87%
“…Larger diameter vessels had lower xylem vulnerability to cavitation. However, it has been demonstrated that xylem vulnerability is not directly correlated with conduit diameter but dependent on pit pore diameter [3,4,13,17]. Wider vessels had a higher probability to have big pit pores and so be more vulnerable to cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…We enclosed them in a black airtight plastic bag to reduce water loss through transpiration and brought them rapidly to the laboratory for hydraulic analysis. In the laboratory, the samples were dehydrated by pressurisation [3][4][5] for 30 to 45 min until sap exudation ceased, then enclosed for at least one hour in a black airtight plastic bag to stop transpiration and remove water potential gradients between leaves and xylem tissues. Ψ xylem was assumed to be the negative of the air pressurisation value.…”
Section: Vulnerability Curvesmentioning
confidence: 99%